PERBEDAAN KADAR ASAM URAT PADA LANSIA MENGGUNAKAN METODE POCT (Point Of Care Testing) DENGAN METODE ENZIMATIK KOLORIMETRI DI PUSKESMAS BANGUNSARI KABUPATEN MADIUN - Desty Ratna , Ayu Pramita; Edy, Haryanto; Syamsul, Arifin (Analis Kesehatan Sains, 2021)
The role of Laboratory examination as a diagnostic of disease is very important, including in determining the amount of uric acid contained in the body. The POCT (Point Of Care Testing) method and the Enzymatic Colorimetric method using a Photometer are several ways that can be done to determine the amount of uric acid content. This study aims to determine the differences in the results of uric acid examination in the elderly using the POCT method with the Enzymatic Colorimetric method at the Bangunsari Health Center, Madiun Regency.This type of research is an analytic observational study with a cross sectional approach. The research population is the elderly who seek treatment at the Bangunsari Health Center, Madiun Regency. The study was carried out in January-May 2021. The research sample consisted of 30 people who were taken by purposive sampling. Research data in the form of primary data obtained directly from the results of laboratory examinations. The data analysis technique used the normality test with the Kolmogorov Smirnov Test and the Independent-Sample T Test.The results showed that the data on uric acid levels in the elderly at the Bangunsari Public Health Center, Dolopo District, Madiun Regency, which was measured using the POCT (Point Of Care Testing) method showed that the mean and standard deviation values ​​were 5,650±1,283 while those measured using the Enzymatic Colorimetric method were 6,340±1,332 indicating that there was an average difference The average results of measuring uric acid levels in the elderly are between those using the POCT (Point Of Care Testing) method and those using the Enzymatic Colorimetric method. Based on the results of the Independent Sample T-test, it is known that the value of Sig. (2-tailed) of 0.046 <0.05, it can be concluded that H0 is rejected and Hi is accepted. That is, there is a significant difference in uric acid levels using the POCT method with the Enzymatic Colorimetric method.